E-Commerce Produk Hasil Pertanian Berbasis Web dengan Metode Agile Software Development - Aldya Bagas Prahastyo; Agung Triayudi; Ben Rahman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
As we know, today's website has become a necessary development for an organization, agency, commercial company, and so on. Web-based applications are applications that can be accessed via a web browser when connected to the internet or intranet network. This application is also software or software that uses programming languages ??such as PHP, CSS and other programming languages. The website is considered effective as an alternative media for marketing as well as providing information to the public, in addition to this online sales and ordering information system, it is expected to improve service to consumers. In this research, an E-Commerce/Online Shop will be developed, the online shop itself is an application for purchasing goods and services through the Internet. Through shopping via the Internet, a buyer can see in advance the goods and services he wants to spend through the web, which is facilitated by the seller. In this webside research I use xampp, with the PHP programming language and use the Agile Software Development method, this method is an approach to systematic and sequential software development that starts at the level and progress of the system throughout Planning, Design, Analysis, Implementation, Testing, Reviews, Releases and applications will be used for farmers for future business